2019
DOI: 10.1021/acs.iecr.9b00314
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Ionic Liquid Capsules for Rapid CO2 Capture

Abstract: The CO 2 absorption by ionic liquids (ILs) were enhanced by the use of hybrid capsules composed of a core of IL and shell of polyurea and alkylated graphene oxide (GO). These composite structures were synthesized using a Pickering emulsion as a template, and capsules of two different ILs were prepared. The contribution of the encapsulated IL on the CO 2 absorption of the capsules is consistent with agitated neat IL, but with an improved mass transfer rate of absorption across different pressures. This novel ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 44 publications
2
60
0
Order By: Relevance
“…First, the capsules and neat IL were placed under vacuum at 20 C for 24 h to remove any dissolved gases. CO 2 capacities were then measured using a previously reported method, 35 in the pressure range of 0-760 torr of CO 2 (resolution <0.05 torr). Briefly, 0.5 g of capsules were added to sample tubes and the headspace was measured by dosing the sample chamber with a known amount of Helium.…”
Section: Co 2 Uptake Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the capsules and neat IL were placed under vacuum at 20 C for 24 h to remove any dissolved gases. CO 2 capacities were then measured using a previously reported method, 35 in the pressure range of 0-760 torr of CO 2 (resolution <0.05 torr). Briefly, 0.5 g of capsules were added to sample tubes and the headspace was measured by dosing the sample chamber with a known amount of Helium.…”
Section: Co 2 Uptake Studiesmentioning
confidence: 99%
“…[32][33][34] For example, CO 2 gas has a relatively high solubility in ILs. [35][36][37] However, most ILs have high viscosities, which limits mass transfer rate and requires agitation of the bulk IL for gas uptake. For example, [Bmim][PF 6 ] is about 300 times more viscous than water (273 cP vs. 0.89 cP for water at 25 C and 1 atm), making it difficult to transfer or pump through a system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Pickering emulsions (i.e., emulsions stabilized by solid particles) as template for the encapsulation of ILs was pioneered by the group of Pentzer. 50,52,53,77,78 This methodology, which employs either graphene oxide (GO) nanosheets or alkylated GO as surfactants, has two main advantages over other encapsulation methods: (a) the drastic reduction in the loading of the surfactant (in Pickering emulsions the surfactant/IL weight ratio is around $1/100, while in the case of systems relying on molecular surfactants this ratio is $1/10); and (b) the use of GO-based surfactants enables both IL-in-water and IL-inoil emulsions to be created, thus allowing the selection of the most appropriate continuous phase for the IL under consideration. The latter advantage is particularly important in the case of ILs (most ILs are hygroscopic) as the possibility of performing the encapsulation in a water-free continuous phase enables the water content in the encapsulated IL to be carefully controlled.…”
Section: Pickering Encapsulationmentioning
confidence: 99%
“…The maximum capacity of primary, secondary, and tertiary aminesupported silica was 0.95, 0.75, and 0.17 mmol CO 2 /g, where our sample shows a high sorption capacity of 54.3 mg CO 2 /g ($1.2 mmol CO 2 /g). Similarly, Huang et al 56 used a polyurea and alkylated graphene oxide IL capsule for CO 2 capture, reporting an absorption of only 3.0 mg CO 2 /g at a pressure of 1.3 bars. More recently, Khdary et al 5 have reported the synthesis of polyvinylidene-uoride-hexauoropropylene (PVDF-HFP) amino-silica composites by a phase separation technique and prepared membranes for CO 2 capture.…”
Section: Carbon Dioxide Capture Capacitymentioning
confidence: 99%